HCV and HIV prevalences strongly correlated in Asian communities with reservoirs of HIV in high-risk groups - Devon D. Brewer; Adnan A. Khan (Journal of Infection in Developing Countries)
Background: In some Asian communities, HIV epidemics initially concentrated in high-risk groups develop into generalized epidemics, while in others HIV epidemics remain confined to high-risk groups. We examined whether blood exposures in a community, as indicated by hepatitis C virus (HCV) prevalence, can account for the variability in HIV prevalence in Asia.